Democratic professionalism in public services - Lethbridge, Jane ca. 20./21. Jh (Policy Press, 2019)
This book explores what it means to act in a democratic way and provides practical guidance which will help public service professionals ensure users are at the centre of public services delivery, drawing from examples of different public services around the world
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Public administration; Civil service positions; Public officers; Professional employees; Berufsethik; Verwaltung